Design and Development of a Universal C-Wrench Special Tool for Assembly and Disassembly of Hydraulic Cylinder Nut Covers - Agung Gema Muhazir; Mohamad Zaenudin; Yasya Khalif Perdana Saleh; Mohammed N. Abdulrazzaq Alshekhly (Department of Mechanical Engineering, Faculty of Engineering and Computer Science, Universitas Global Jakarta, 2026)
Maintenance and repair of hydraulic cylinders, especially in confined areas like those in articulated dump trucks, can be very difficult because of access to tools and safety issues. In this study, the design and development of a Universal C-Wrench, a special tool for the safe and efficient assembly/ disassembly of hydraulic cylinder nut covers without removing the entire cylinder from the equipment were presented. An engineering design process (EDP) was used, which includes problem identification, requirement analysis, conceptual design, design selection, detailed design, prototyping and simulation-based validation. Three different design approaches were formulated, based on mechanical performance using finite element analysis (FEA), cost estimation, and field applicability. The final concept was chosen as Design 2, which was made of SS400 steel and had the lowest safety factor (12.075) that was still above the standard requirement for static load-bearing tools. Other improvements including dimensional changes, structural reinforcement and the implementation of dual handles for increased ergonomics were made based on field use and usability. Overall, the Universal C-Wrench is a versatile and cost-effective tool for servicing hydraulic cylinders in heavy machinery and could be used in other similar industrial applications.